Pengaruh Current Ratio, Total Asset Turn Over terhadap Harga Saham Sektor Industri Baja & Besi yang Terdaftar di Bursa Efek Indonesia - Aina Mawa; Suryanto Sosrowidigdo; Siti Nurjanah (International Forum of Researchers and Lecturers, 2026)
Stock prices are one of the key indicators that reflect a company’s performance and value in the eyes of investors. This study aims to identify and analyze the impact of the Current Ratio (CR) and Total Asset Turnover (TATO) on stock prices for companies in the Steel and Iron Industry Sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2025, both individually and simultaneously. This study employs a descriptive quantitative approach using secondary data in the form of annual financial statements from nine sample companies selected through purposive sampling, resulting in 45 observations. The data analysis techniques used include classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and the coefficient of determination (R²). has a significant effect on stock price. Total Asset Turnover also has a positive and significant effect on stock price. Simultaneously, the Current Ratio and Total Asset Turnover have a significant effect on stock prices, with a coefficient of determination (R²) of 0.332, indicating that these two independent variables account for 33.2% of the variation in stock prices, while the remaining 66.8% is influenced by other factors outside the scope of this study.